The 500 [compact disc, unabridged] : a novel - Quirk, Matthew (Hachette Audio, 2012)
Mike Ford turned himself around and worked his way into Harvard Law School. Now he is employed by the Davies Group, Washington's most high-powered and well-respected strategic consulting firm that specializes in pulling strings and peddling influence for the people who really run Washington. Quickly pulled into a seductive, dangerous web of power and corruption, Mike struggles to find his way out. But how does one save his soul when he has made a deal with the devil?